Twenty Years After International Conference on Population and Development: Where Are We With Adolescent Sexual and Reproductive Health and Rights? - Chandra-Mouli, Venkatraman; Svanemyr, Joar; Amin, Avni; Fogstad, Helga; Say, Lale; Girard, Françoise; Temmerman, Marleen (Journal of adolescent health, 2015)
The International Conference on Population and Development in Cairo in 1994 laid out a bold, clear, and comprehensive definition of reproductive health and called for nations to meet the educational and service needs of adolescents to enable them to deal in a positive and responsible way with their sexuality. In the context of the ongoing review of the International Conference on Population and Development Programme of Action and the considerations for a post-2015 development agenda, this article summarizes the findings of the articles presented in this volume and identifies key challenges and critical answers that need to be tackled in addressing adolescent sexual and reproductive health and rights. The key recommendations are to link the provision of sexuality education and sexual and reproductive health (SRH) services; build awareness, acceptance, and support for youth-friendly SRH education and services; address gender inequality in terms of beliefs, attitudes, and norms; and target the early adolescent period (10–14 years). The many knowledge gaps, however, point to the pressing need for further research on how to best design effective adolescent SRH intervention packages and how best to deliver them.